PELATIHAN AKUNTANSI PERANGKAT DESA GUNA PENINGKATAN KETERAMPILAN PENGELOLAAN KEUANGAN DI DESA KADUAGUNG BARAT, BANTEN - Afridayani; Setianingsih; Adhitya Putri Pratiwi (Jurnal Abdikaryasakti, 2024)
Village funds are a form of government attention in providing opportunities to villages as an effort to maintain their potential. The use of village funds is directed at financing development and community empowerment with the aim of improving the welfare of village communities, the quality of human life and overcoming poverty. However, the amount of village funds needs to be balanced with increasing the capacity of Human Resources, namely village officials as managers of village funds. The low quality of Human Resources will ultimately give rise to community concerns regarding the management of village funds whose placement is used for other things that are not in accordance with the initial objectives. The aim of this Community Service activity is to provide training to partners, in this case Kaduanggung village officials, Banten, especially regarding: (1) Understanding accounting concepts, especially regarding village funds, and (2) Understanding the importance of transparency in financial management . This service activity is planned as an ongoing program, so that at the end of the assistance it is hoped that village officials will have full awareness regarding accounting records in managing village funds, and have records that are in accordance with accounting principles. Apart from that, to realize healthy village fund governance, active community participation is needed in carrying out supervision. The implementation of this service consists of several stages of activities, namely socialization, consultation and mentoring, formation of a village finance team, to ongoing evaluation and monitoring. The feedback and evaluation carried out is in the form of ongoing monitoring related to the recording carried out in the use of village funds.